PEMETAAN POTENSI KAWASAN WISATA PANTAI PULAU DUA KECAMATAN BAKONGAN TIMUR KABUPATEN ACEH SELATAN - Muhammad Kabul Rahman; Ahyuni Ahyuni; Endah Purwaningsih (JURNAL BUANA, 2020)
This study aims to determine: (1) Physical potential of the coastal tourism area in Pulau Dua, East Bakongan District, South Aceh Regency. (2) What attractions can be developed in the coastal tourism area on Pulau Dua, East Bakongan District, South Aceh Regency. This type of research is classified into quantitative descriptive research. This study uses a scoring method for each parameter of each sample point that has been observed and measured in the field. Determination of the level of suitability is obtained from the multiplication of scores and weights of each parameter. The suitability class of the beach tourism area can be seen from the suitability percentage obtained by the sum of the values ​​of all parameters. The research results obtained are: (1) based on the sum of the scores of each parameter, the suitability of the region for the physical potential of the coastal area on Pulau Dua has a value of 139 with a Very Appropriate category. (2) Attractions that can be developed on Pulau Dua are beach recreation, beach sports, boating, sunbathing, fishing, swimming.